Association between gut microbiota and allergic rhinitis: a systematic review and meta-analysis - Mengyao Li; Qian Wang; Ruikun Wang; Jian Pu; Yimin Zhang; Siyu Ye; Jieqiong Liang; Tao Li; Qinglong Gu (PeerJ)
Background Many studies have shown that allergic rhinitis (AR) is closely related to intestinal flora, and probiotics are effective in treatment. However, the results of human observational studies on the correlation between intestinal flora and AR have been contradictory. The aim of this study was to determine the relationship between gut microbiota and allergic rhinitis and to provide a clinical reference. Methods PubMed, Web of Science, Medline, Embase, Cochrane Library, and Cinahl databases were searched, and the literature on the correlation between allergic rhinitis and the gut microbiota reported from database establishment to December 2023 was included. Literature meeting the inclusion criteria was screened, and meta-analysis of the included literature was performed using R software (4.3.3). Literature quality underwent assessment utilizing the Newcastle-Ottawa Quality Assessment Scale. Hedge’s g standardized mean difference (SMD), confidence intervals (CIs), and heterogeneity (I2) for alpha diversity were calculated. Median interquartile range (IQR) were calculated as effect statistics for the abundance of bacteria. The Egger test determined publication bias in the literature. Results A total of 10 observational studies in humans were conducted, identifying 550 patients with AR and 385 healthy individuals. No statistically significant differences were observed in alpha diversity between two groups, including Shannon index (SMD = −0.3938, 95% CI [−0.9847–0.1972], I2 = 94%), Simpson index (SMD = −0.16, 95% CI [−1.12–0.80], I2 = 96%) and Chao1 index (SMD = −0.00, 95% CI [−1.32–1.32], I2 = 97%). We performed a meta-analysis for the following four phyla, but found no significant differences: Firmicutes (95% CI [−0.10–0.19], I2 = 75%), Bacteroidetes (95% CI [−0.42–0.19], I2 = 95%), Proteobacteria (95% CI [−0.06–0.03], I2 = 92%), Actinobacteria (95% CI [−0.09–0.03], I2 = 83%). Conclusions The currently available evidence does not suggest that patients with allergic rhinitis may have similar intestinal flora imbalances. Nevertheless, further corroboration is required with larger samples and higher-quality studies.